DEVELOPING NIION INSTAGRAM CONTENT FOR INCREASING CUSTOMER ENGAGEMENT (The Indonesian Journal of Business Administration, 2019)
In Indonesia, the internet users and active social media is riding into a half of the total population of the country which is 150 million people. Report said that the most active social media platforms are Youtube, Facebook, Whatsapp, and Instagram. Indonesia is reportedly has become the biggest market for Instagram in Asia Pacific with no less than 60 million people logging on. In Instagram, people able to take real action, not only follow accounts, give likes, or comment, but Instagram can also convince users to click on links to sites to buy product. Research said that the most happening market on the global front is the personal accessories market which majorly comprises of jewelry, bags, watches, and etc (Based on data from Statista, 2019).PT NIION Indonesia Utama is one of the local brands which manufactures bags with various models such as sling bags, duffle bags, hip bags, and many more. The signature of NIION is that it is also providing full colours of bags starting from red, yellow, green, navy, white, black, pink, grey, orange, chocolate, and many more. Although NIION having a lot of followers in Instagram, and always participates in many events, NIION’s engagement rate in Instagram still in the low level that makes the sales of NIION is also under the expectation.To further understand the issues, this study has been used a series of analysis from external and internal environment analysis to consumer analysis using an exploratory sequential mixed method for a combination of both exploratory and descriptive research as the primary data, including the SWOT Analysis and Root Cause Analysis. The exploratory research done by conducting focus group discussion with the suitable target segment to get insight for the factors that can be affected to increasing the customer engagement and sale. After doing the exploratory research, the findings used to build a questionnaire for descriptive research. Then, the questionnaire will be spreading in to minimum of 200 respondents as needed for problem-solving research. To analyse the descriptive research, the data will be processed with SPSS to find what independent factors that has significant score to dependent factors which is customer engagement.The proposed solution to the problem are: a new STP and Marketing Mix Strategies, including the results from the data that show the factors that can affected customer engagement such are Detail Specific content, Responsible content, Fun and Cinematic content, also Collaboration content. The findings chosen according to the company’s circumstances and is expected to be able to solve the problem in engagement rate when the solution of the findings is implemented by NIION after developing the new design of content for its Instagram.Keywords: customer engagement, Instagram, social media content, fashion.